Personal digital library system / Muhammad Syaufik Shith - Shith, Muhammad Syaufik (2005)
Personal digital hbrary represents a system that can manage all personal resources collection such as books, journal, theses and magazines. This system has been developed to give a solution for FTMSK lecturers in managing their resources. Mostly, lecturers in FTMSK have their ovm collection of resources. They also involve with many research and others education activities. They need a system that allowed them to share, search and borrow among them. The objective of this study is to develop a web based application that can help lecturers to manage their resource efficiency. It also focuses on to develop an electronic librarian functions that allows the lecturers to searching, sharing, borrowing, and promoting their materials among them. The methodology of this study is based on System Development Life Cycle (SDLC). By doing the study on system analysis, creating requirement modeling, object modehng, data and process modeling, it help researcher for fully understand and developing the system. It also involves designing the interface of the system according to HCI. By refer to those modeling, it easily and help the researcher to develop the system. At the end of the study, the researcher hope the system can help lecturers in managing their resources efficiently. .